The Repertoires of Peptides Presented by MHC-II in the Thymus and in Peripheral Tissue: A Clue for Autoimmunity? - Collado, Javier A.; Guitart, Carolina; Ciudad, M. Teresa; Alvarez, Iñaki; Jaraquemada, Dolores (Frontiers in Immunology, 2013)
T-cell tolerance to self-antigens is established in the thymus through the recognition by developing thymocytes of self-peptide-MHC (pMHC) complexes and induced and maintained in the periphery. Efficient negative selection of autoreactive T cells in the thymus is dependent on the in situ expression of both ubiquitous and tissue-restricted self-antigens and on the presentation of derived peptides. Weak or inadequate intrathymic expression of self-antigens increases the risk to generate an autoimmune-prone T cell repertoire. Indeed, even small changes of self-antigen expression in the thymus affect negative selection and increase the predisposition to autoimmunity. Together with other mechanisms, tolerance is maintained in the peripheral lymphoid organs via the recognition by mature T cells of a similar set of self-peptides in homeostatic conditions. However, non-lymphoid peripheral tissue, where organ-specific autoimmunity takes place, often have differential functional processes that may lead to the generation of epitopes that are absent or non presented in the thymus. These putative differences between peptides presented by MHC molecules in the thymus and in peripheral tissues might be a major key to the initiation and maintenance of autoimmune conditions.